Improving DFN-geomechanical model integration using a novel automated approach. (January 2019) - Karimi Sharif, Ladan; Elmo, Davide; Stead, Doug
Abstract: In the past decade, numerical modelling has been increasingly used for simulating the mechanical behavior of naturally fractured rock masses. The synthetic rock mass approach often adopted has three main components: data collection and characterisation; discrete fracture network (DFN) modelling; and finally, geomechanical modelling to simulate rock mass behaviour. The focus of this paper is the integration of the DFN with geomechanical models, with emphasis on the numerical aspects of embedding rather complex 2D fracture networks within a finite element mesh. A new method is introduced that simplifies fracture networks, while maintaining important fracture properties such as orientation, connectivity, and intensity. The resulting finite element mesh is of sufficient quality to both improve computational time and eliminate spurious results that may be associated with the presence of highly distorted elements. The proposed method uses a web-based code with two integral components (DFNAnalyzer and DFNCleaner) that analyse the properties of the original fracture network, and then perform simplifications to ensure an acceptable (user defined) mesh quality is achieved.